Amorphous cobalt silicate nanobelts@carbon composites as a stable anode material for lithium ion batteries. Issue 12 (7th September 2015) - Cheng, Wei; Rechberger, Felix; Ilari, Gabriele; Ma, Huan; Lin, Wan-Ing; Niederberger, Markus
Abstract : Amorphous cobalt silicate nanobelts@carbon composites turned out to be excellent anode materials for lithium ion batteries. Abstract : During the past decade, tremendous attention has been given to the development of new electrode materials with high capacity to meet the requirements of electrode materials with high energy density in lithium ion batteries. Very recently, cobalt silicate has been proposed as a new type of high capacity anode material for lithium ion batteries. However, the bulky cobalt silicate demonstrates limited electrochemical performance. Nanostructure engineering and carbon coating represent two promising strategies to improve the electrochemical performance of electrode materials. Herein, we developed a template method for the synthesis of amorphous cobalt silicate nanobelts which can be coated with carbon through the deposition and thermal decomposition of phenol formaldehyde resin. Tested as an anode material, the amorphous cobalt silicate nanobelts@carbon composites exhibit a reversible high capacity of 745 mA h g −1 at a current density of 100 mA g −1, and a long life span of up to 1000 cycles with a stable capacity retention of 480 mA h g −1 at a current density of 500 mA g −1 . The outstanding electrochemical performance of the composites indicates their high potential as an anode material for lithium ion batteries. The results here are expected to stimulate further research into transition metal silicate nanostructures for lithium ion battery applications.